Naturalised vertebrates in Peru: history and state of knowledge - Cossíos, E. Daniel (2010)
Despite the importance of the impacts of the exotic species on the native biodiversity, these have been little studied in South America. In Peru, the information published on the subject is scarce and is many times restricted to gray literature, complicating the analysis of the problem and the wildlife management. In this publication 23 species of vertebrates naturalized in Peru were identified, and the known information on its dispersion in the country, current distribution and impacts on natural environments was summarized. In addition, 8 species that were object of failed intents of introduction to natural environments or whose naturalized populations were extinguished were identified, as well as 10 species of vertebrates whose naturalization is probable but should be verified. This information could be the base for the creation of a research plan on the naturalized vertebrates in Peru and their impacts.